Type‐I interferons mediate the neuroinflammatory response and neurotoxicity induced by rotenone. Issue 1 (April 2017) - Main, Bevan S.; Zhang, Moses; Brody, Kate M.; Kirby, Francis J.; Crack, Peter J.; Taylor, Juliet M.
Abstract: Evidence from post‐mortem human brains, animal studies and cell culture models has implicated neuroinflammation in the aetiology of chronic neuropathologies including Alzheimer's and Parkinson's diseases. Although the neuroinflammatory response is considered detrimental in contributing to these pathologies, the underlying mechanisms are still not well understood. The type‐I interferons (IFNs) have been well characterised in the periphery and are known to initiate/modulate the immune response. Recently, they have been implicated in ageing and we have also demonstrated increased type‐I IFN expression in post‐mortem human Alzheimer's and Parkinson's disease brains. We hypothesise that the type‐I IFNs are key drivers of the damaging, self‐perpetuating pro‐inflammatory response that contributes to these chronic neuropathologies. In support of this, we have recently confirmed in models of Alzheimer's and Parkinson's disease that mice lacking the type‐I IFN receptor (IFNAR1), display an attenuated neuroinflammatory response with subsequent neuroprotection. To further investigate type‐I IFN‐mediated neuroinflammation and the specific CNS cell types involved, this study treated primary cultured wild‐type and IFNAR1 −/− neurons or mixed glia with the mitochondrial complex I inhibitor, rotenone. Wild‐type neurons and glia treated with 3 nM and 25 nM rotenone, respectively, exhibited a pro‐inflammatory response, including increased type‐I IFN expression that was attenuated in cells lacking IFNAR1. Reduced type‐I IFN signalling in IFNAR1 −/− neurons also conferred protection against caspase‐3‐mediated rotenone‐induced cell death. Further, this reduced pro‐inflammatory response in the IFNAR1 −/− glia subsequently diminished their neurotoxic effects to wild‐type neurons. In support of this, we confirmed that therapeutically targeting the type‐I IFN glial response to rotenone through a specific IFNAR1 blocking monoclonal antibody was neuroprotective. Our data has confirmed that both neurons and glia contribute to the pro‐inflammatory response induced by rotenone with attenuation of this response beneficial in reducing neuronal cell death. Read the Editorial Comment for this article onpage 9 . Abstract : We confirm the mitochondrial complex I inhibitor, rotenone induces both a type‐1 IFN and pro‐inflammatory response (increased TNF‐α, IL‐1β, IL‐6 expression) in primary cultured neurons and mixed glia. This response was attenuated in cells lacking the type‐1 IFN receptor, IFNAR1, with IFNAR1 −/− neurons also neuroprotected against cell death induced by rotenone. Targeting this detrimental response through the use of IFNAR1 −/− glia or a blocking monoclonal antibody to IFNAR1, conferred protection against rotenone‐induced neuronal cell death. Read the Editorial Comment for this article onpage 9 .